Pengaruh Likuiditas, Profitabilitas, Dan Aktivitas Terhadap Return Saham Dengan Moderasi Kebijakan Dividen - Cynthia Margaretha Putri, Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2021)
This research aims to determine how the ability of the dividend policy variable to moderate the effect of the liquidity, profitability and activity variables on stock returns in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. The sample used was purposive sampling method and valid data were 52 companies. The data processing technique uses multiple regression analysis assisted by the  Eviews 10 for Windows and Microsoft Excel 2010 program. The results of this research show that the profitability variable does not affect stock returns, while the liquidity and activity variables have an effect on stock returns. Dividend policy is unable to moderate the relationship between liquidity, profitability, and activity on stock returns. The implication of this research is the need for in-depth information for investors in choosing investments to pay more attention to the factors that affect the company's return in the long term.